UMP business application - Muhammad Nabil Fikry, Rohyzat (2015)
This paper presents the UMP Business Application as an application that can work in any mobile devices that runs on Android. Nowadays, everyone is using mobile phone. And from my observation, students from University Malaysia Pahang love to do business. So, I find these two criteria are wise enough for me to create an app for UMP students as a platform for them to do their business activity, buying and selling stuffs online. I also find that students more tends to use wrong medium to promote their business such as e-Comm. Thus, it makes me more passionate in developing this mobile application. This paper investigates about problem that occurs nowadays and finally it proposed the UMP Business Application to prevent this problem from occurs again. I hope that this application can ease UMP student's business activity and everyone is happy with it.